Integrated productivity in urban Africa : introducing the neo-mercantile planning theory - Okeke, Donald (Urban book series (Springer (Firm)), 2016)
This book introduces readers to neo-mercantile planning theory in the context of spatial regional integration in Africa. It proposes a new approach that rethinks neo-liberalism as the meta-theory of planning in Africa, and pioneers an original school of thought that presents a general theory of planning for Africa in the twenty-first century. Research to substantiate the new theory was conducted over the period November 2010 to May 2015 and is presented here in four sections with more than 500 references. The book offers comprehensive coverage, from the theoretical foundations and framework, through application and empirical research, to analysis, conclusions and recommendations.